MIKROENKAPSULASI PELET PROBIOTIK DENGAN METODE SUSPENSI UDARA MENGGUNAKAN FLUIDIZED BED DRYER (FBD) - ADLIA , AMIRAH
Lactobacillus acidophilus were completely inactive when exposed to gastric acid condition at pH 1.2. Microencapsulation of the bacterial cells by air suspension method using Fluidized Bed Dryer (FBD) was proposed to develop technology of powder production of probiotics which can increase the survivability of probiotics in gastrointestinal system. Cells suspension was dispersed in Avicel pH 101 followed by extrusion-spheronization at ambient temperature to create pellet as a matrix that protects the probiotic in the subsequent coating using FBD at 37oC, 2-3 atm air pressure. Cell-encapsulated pellets with 280-500 3m size were film coated using sodium alginate solution-internally crosslinked with CaCl2 at various ratios. Gastric resistant permeability of the coating film was tested by using riboflavine 5'-phosphate sodium as a model. The concentration of riboflavine leached out from riboflavine microcapsules upon exposure to artificial gastric fluid was measured by spectrophotometer UV 267 nm. Encapsulated L. acidophilus were incubated in MRS Broth pH 1.2 at 37oC and sampled every 60 minutes to analyze the viability of L. acidophilus in gastric acid condition. Viable bacterial cells were enumerated by Total Plate Count technique. The optimum formula resulted in good characteristic of probiotic microcapsule was using 1.5% (w/v) sodium alginate and 1.7% (w/v) CaCl2 in HCl pH 3 where cell's population reducted only 1 log. The microencapsulation was effectively preserved probiotic cell viability at 90% of cell's population as compared to non-encapsulated cells and therefore potential for delivering the viable cells to intestine.